2007
DOI: 10.1093/heapol/czm007
|View full text |Cite
|
Sign up to set email alerts
|

Social franchising of TB care through private GPs in Myanmar: an assessment of treatment results, access, equity and financial protection

Abstract: This article assesses whether social franchising of tuberculosis (TB) services in Myanmar has succeeded in providing quality treatment while ensuring equity in access and financial protection for poor patients. Newly diagnosed TB patients receiving treatment from private general practitioners (GPs) belonging to the franchise were identified. They were interviewed about social conditions, health seeking and health care costs at the time of starting treatment and again after 6 months follow-up. Routine data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 10 publications
3
67
0
4
Order By: Relevance
“…These results are in conformity with the findings of other studies. 11,12 In the present study, pulmonary TB was found in 80.70 % and extra pulmonary in 19.30% patients which is almost similar to the finding of another study conducted in Thailand where corresponding figures were 77% and 23% respectively. 13 Similar trend was revealed in a study conducted in Meerut (PTB 91.70% and extra pulmonary in 8.30%) 10 and in another study of Howrah (pulmonary cases 86.70% and extra pulmonary cases 13.30%).…”
Section: Discussionsupporting
confidence: 90%
“…These results are in conformity with the findings of other studies. 11,12 In the present study, pulmonary TB was found in 80.70 % and extra pulmonary in 19.30% patients which is almost similar to the finding of another study conducted in Thailand where corresponding figures were 77% and 23% respectively. 13 Similar trend was revealed in a study conducted in Meerut (PTB 91.70% and extra pulmonary in 8.30%) 10 and in another study of Howrah (pulmonary cases 86.70% and extra pulmonary cases 13.30%).…”
Section: Discussionsupporting
confidence: 90%
“…A research results from Lo¨nnroth, Aung, Maung, Kluge, and Uplekar (2007) concluded that TB program services are better through franchise clinics. This study suggests that social franchising of TB care can contribute positively to public health, including equity in access to quality care and financial protection for the poor.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in TB case notification after involvement of private providers have also been reported by studies in Vietnam (18%), 20 Nepal (92%), 21 India (11%), 22 and Myanmar (21%). 23 The differences between these increases are likely caused by differences of context (e.g., TB incidence, baseline case notification, care seeking behavior), general intervention characteristics and task mix (e.g., suspect referral, treatment by PPs), and output (e.g., number, type and distribution of private providers effectively engaged). Furthermore, it is not appropriate to fully attribute the incremental effectiveness in all these studies to the PPs strategies.…”
Section: Discussionmentioning
confidence: 99%